Liquidity and mortality of low-wage workers: evidence from wage allowances in Brazil - Castro, Caio Pedro de Almeida Silva (2022)
We study whether workers in Brazil likely to be liquidity-constrained experience more fatal events in the week they receive a payment when compared to other weeks. Using restricted access data and leveraging a federal transfer program (Abono Salarial) with quasi-random payment date assignment for identification, we find that weeks of payment have over 9.5\\% more mortality counts for the group being paid than other weeks, when compared to individuals not being paid in such week, with results being estimated by a Poisson regression. Using a Regression Discontinuity Design, we estimate an increase of 10 p.p. in the probability of dying in the 15 days following payment versus dying any other day for those marginally eligible, when compared to those almost eligible. These results are concentrated in causes of death more intimately related to economic activity, and stem from individuals in municipalities more likely to be credit constrained.